2022
DOI: 10.3390/ijms232315159
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Revealed Antimicrobial Mechanisms of Lactobacillus rhamnosus SCB0119 against Escherichia coli and Staphylococcus aureus

Abstract: Lactic acid bacteria were reported as a promising alternative to antibiotics against pathogens. Among them, Lactobacillus rhamnosus could be used as probiotics and inhibit several pathogens, but its antibacterial mechanisms are still less known. Here, L. rhamnosus SCB0119 isolated from fermented pickles could inhibit bacterial growth or even cause cell death in Escherichia coli ATCC25922 and Staphylococcus aureus ATCC6538, which was mainly attributed to the cell-free culture supernatant (CFS). Moreover, CFS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Specifically, hierarchical clustering analysis of the compounds released by the four lactic acid bacteria shows for L. RHA and L. AC specific areas of significantly overexpressed metabolites, which strongly differ from the same areas of the other lactic acid bacteria. It has been shown that CFS from L. RHA strain SCB0119 altered the transcription profiles of several genes involved in fatty acid degradation, ion transport, and the biosynthesis of amino acids in Escherichia coli, as well as fatty acid degradation, protein synthesis, DNA replication, and ATP hydrolysis in Staphylococcus aureus, which are important for bacterial survival and growth [23]. In addition, L. RHA colonization of the epithelial cells has been demonstrated as being responsible for drastic changes in the metabolic environment, forcing metabolic adaptation in C. albicans and reducing fungal virulence [9].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, hierarchical clustering analysis of the compounds released by the four lactic acid bacteria shows for L. RHA and L. AC specific areas of significantly overexpressed metabolites, which strongly differ from the same areas of the other lactic acid bacteria. It has been shown that CFS from L. RHA strain SCB0119 altered the transcription profiles of several genes involved in fatty acid degradation, ion transport, and the biosynthesis of amino acids in Escherichia coli, as well as fatty acid degradation, protein synthesis, DNA replication, and ATP hydrolysis in Staphylococcus aureus, which are important for bacterial survival and growth [23]. In addition, L. RHA colonization of the epithelial cells has been demonstrated as being responsible for drastic changes in the metabolic environment, forcing metabolic adaptation in C. albicans and reducing fungal virulence [9].…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen from the overall clustering results that different treatment conditions caused the upregulation and downregulation of some genes involved in the same biological process, indicating that some metabolic processes or cellular pathways play a role in the process of cells being treated with hesperetin. [28]. The volcano plots of the hesperetin-treated and control groups are depicted in Figure 4A.…”
Section: Transcriptomic Effects Of Hesperetin On a Acidoterrestris 34...mentioning
confidence: 99%